Automatiserat flaggningssystem för proaktivt medicintekniskt patientsäkerhetsarbete - Brasch,Wilma; Martinsson,Ida (2025)
Patient safety is a key component in healthcare, in particular within the widespread use of medical technology. A proactive approach to patient safety in medical technology is essential for fulfilling the healthcare system’s duty to protect patients from harm. At the department Digitalisering IT och MT at Region Skåne, all proactive patient safety efforts are currently handled manually. The aim of this project is to investigate the possibility of developing an automated flagging system that can detect anomalies within the region’s existing system Ritz. If feasible, the project also aims to design a detailed description of such a system. The work began with interviews to map current procedures and an analysis of existing systems. As a limitation the flagging system was then restricted to only identifying an increased frequency of anomalous events related to specific device models. Next, a formula was developed that primarily considers parameters such as number of reported anomalous events and devices in operation to form the basis of the flagging mechanism. An iterative process followed to form a data flowchart possible to implement in Ritz. The process concluded that the prerequisites for a flagging system are in place, resulting in a complete and implementable flowchart. An interface with a focus on user experience was designed and historical data was statistically analyzed to determine appropriate threshold values. After evaluation, thresholds were set to the mean plus one standard deviation. Further, several development opportunities were identified during this project, as well as some deficiencies that may affect the performance of the system negatively. Lastly, implementation of the flagging system is expected to support patient safety coordinators and enable a proactive approach to patient safety.
Keywords: flaggningssystem; patientsäkerhet; avvikelser; incidenter; medicinsk teknik; gränsvärden; tröskelvärden